Employing keywords and lexical bundles within figure captions in earth science research articles - Tsaqifa, Tsabita Intan; Roselani, Ni Gusti Ayu (Universitas Dian Nuswantoro, 2024)
The presentation of data is considered an essential part of academic writing, especially in research articles, and it could not stand alone without a short text to describe the visual data, namely figure legends. This research aims to identify the keywords and lexical bundles frequently used in figure legends. In addition, this research also examines the functions conveyed by these linguistic features. Based on the identification of the corpus, there are 334 keywords found with the 20 highest frequencies belonging to the terminologies frequently used in earth science (fault, seismic, quartz, and formation) and words related to the visual representation of the figure legends (line/lines, map, area, figure and legend). Furthermore, noun-related bundles are found to be the greatest number for lexical bundles, with 165, followed by verb-related bundles with 79, clause-related bundles with 54, and preposition-related bundles with 17. These lexical bundles perform research-oriented, text-oriented, and participant-oriented functions. These findings suggest that lexical bundles play a role in explaining the research condition, connecting visual data and research results discussed in research articles, and displaying information about visual data or specific parts of research articles to readers.